IGBT lifetime model considering composite failure modes. (1st June 2022) - Li, Lie; He, Yigang; Wang, Lei; Wang, Chuankun; Liu, Xiaoyan
Abstract: As a new generation of power devices, IGBT devices are widely used in fields such as aerospace, power transmission and transformation. Failures happen to the modules under different mechanisms and temperature conditions, but the current practice rarely considers the interaction of multiple failure mechanisms in the lifetime model, leading to an over optimistic lifetime prediction. With the analysis of the IGBT failure mechanism, this paper studies the IGBT's overall failure probability distribution assuming the failure of bonding wire and solder layer follows Weibull distribution. By exploring the impacts of the Weibull parameters, the relationship between the lifetime of each failed component and the IGBT's overall lifetime is quantified with the fitted coupling coefficients. The analyzing results show that when the bonding wire and the solder layer have similar lifetime, the IGBT's whole lifetime will be reduced, and the reduction degree is affected by the shape parameters of Weibull distribution, up to 30%. The IGBT lifetime model considering coupling effect is then established, which is verified by the experiments. The experimental results prove the existence of coupling effect, as well as the superiority of the model in lifetime prediction, whose error is reduced by 4.1% compared with that without coupling effect.